The Slovene Road into Europe (Czech Journal of International Relations, 2000)
Slovenia was established in 1991 by its secession from the Yugoslav Federation. This was preceded by various events which we can classify as economic, social, politico-economic and international policy causes. They determined the modus operandi of the new state in international policy and alongside traditions dating back to the Austro-Hungarian monarchy, the first and second Yugoslavia, they were the starting point of its foreign policy.The first foreign policy representation decided that a small state such as Slovenia needed to be anchored in international structures, above all, by its membership in international governmental organizations, whether of a worldwide or regional nature (UN, WTO, the Council of Europe, OSCE, the IMF, BRD, CEFTA, CEI and others). Slovenia intends to be a standard democratically and economically advanced country and its efforts along this road are undeniable. Good relations with its neighbours (Italy, Croatia, Austria and Hungary) are important for Slovene foreign policy, although certain disputes still need to be settled with the two former, possibly with the first three mentioned countries. Slovenia’s priority in the security dimension is membership in NATO. The economic priority of the country’s foreign policy is membership in the European Union (EU) even though certain alternatives of integration have been discussed. An application for membership in the EU has been submitted in June 1996 and intensive negotiating processes are currently in progress.The Czech Republic and Slovenia have certain common problems on their road to the EU (for example, in the field of transformation, relations with their neighbours economic development, the assessment of the Commission, etc.). Public opinion and political parties in the Czech Republic and in Slovenia mainly support accession to the EU.Among all the candidates, Slovenia is among the economically most advanced countries (it was included in the first wave as it prevailed at the time) and its chances to be accepted are not negligible.